2021
DOI: 10.1186/s12865-021-00449-1
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral regulatory T cells from colon cancer patients comprise several activated effector populations

Abstract: Background Intratumoral regulatory T cells (Treg) in colon cancer are a heterogeneous cell population, with potential impact on patient outcome. Generally, a high Treg infiltration has been correlated to a worse patient outcome, but it is still unclear how the composition of different Treg subsets affects patient relapse and survival. In this study, we used mass and flow cytometry to characterize Treg in colon tumors and corresponding unaffected tissue, followed by a correlation to clinical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…As already discussed, TI-Treg cells express high levels of CD39/CD73 ectonucleotidases that convert ATP to adenosine, a potent suppressor of tumor immunity (Figure 1f) (258). CD39+ TI-Treg cells have been found to play an important role during CRC tumor growth (150) and inhibition of CD39 enzymatic activity has been evaluated in a CRC hepatic-metastatic murine model. Here, CD39+ Treg cells modulate NK reactivity against the tumor, and targeting CD39 was found to both inhibit Treg cell activity in vitro and reduce tumor growth in vivo (259).…”
Section: Therapeutic Approaches To Target Treg Cells In Crcmentioning
confidence: 87%
See 2 more Smart Citations
“…As already discussed, TI-Treg cells express high levels of CD39/CD73 ectonucleotidases that convert ATP to adenosine, a potent suppressor of tumor immunity (Figure 1f) (258). CD39+ TI-Treg cells have been found to play an important role during CRC tumor growth (150) and inhibition of CD39 enzymatic activity has been evaluated in a CRC hepatic-metastatic murine model. Here, CD39+ Treg cells modulate NK reactivity against the tumor, and targeting CD39 was found to both inhibit Treg cell activity in vitro and reduce tumor growth in vivo (259).…”
Section: Therapeutic Approaches To Target Treg Cells In Crcmentioning
confidence: 87%
“…The subgroups with the highest and intermediate expression of CD39 were found in the tumor, while the subgroup with the lowest expression was found in healthy colon tissue. Higher expression of CD39 correlated with poorer outcome (150).…”
Section: Tumor-infiltrating Treg Cells and Crcmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to other solid tumors, high levels of tumor-infiltrating FoxP3 + Tregs were related with increased survival in CRC patients [ 9 , 24 ]. Recent studies reported that tumor-infiltrating CD39 + Tregs in CRC patients expressed different markers such as OX-40, CTLA-4 and ICOS, implicating their high immunosuppressive abilities in inhibiting anti-tumor immune responses [ 25 , 26 ]. Correale et al, showed that a higher level of FoxP3 + T-lymphocyte tumor infiltration in CRC patients receiving chemotherapy or chemo-immunotherapy was a favorable prognostic marker [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of Tregs in CRC is nuanced and context-dependent, as Tregs can also protect the mouse and human host from cancer-associated inflammation 162 , 163 and BLIMP-1+ Tregs and Treg-derived IL-10 have been associated with decreased polyps and increased CRC survival in both mice and humans 164 166 . Together, these conflicting results suggest that distinct Treg subsets may perform different functions in intestinal cancers 167 , 168 . For example, in mice, Treg-specific loss of transcription factor TCF-1 expression, a suppressor of genes co-bound by FoxP3, increases Treg-mediated T cell suppression and promotes tumor growth in polyposis, demonstrating a role for Treg TCF-1 expression in tumor clearance 169 .…”
Section: Gastrointestinal Tract Tissue Tregsmentioning
confidence: 99%